Stress proteins: nomenclature, division and functions - Kopeček, Petr; Altmannová, Karla; Weigl, Evžen (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2001)
The heat shock response, characterized by increased expression of heat shock proteins (Hsps) is induced by exposure of cells and tissues to extreme conditions that cause acute or chronic stress. Hsps function as molecular chaperones in regulating cellular homeostasis and promoting survival. If the stress is too severe, a signal that leads to programmed cell death, apoptosis, is activated, thereby providing a finely tuned balance between survival and death. In addition to extracellular stimuli, several nonstressfull conditions induce Hsps during normal cellular growth and development. The enhanced heat shock gene expression in response to various stimuli is regulated by heat shock transcription factors.
Keywords: genetická transkripce; terminologie jako téma; Transcription, Genetic; Terminology as Topic; Heat-Shock Response; reakce na tepelný šok; Animals; Heat-Shock Proteins; Humans; lidé; zvířata; proteiny teplotního šoku